The individual in the economic and monetary union : a study of legal accountability / Ana Bobić. - Bobić, Ana, 1987- (Cambridge University Press, 2024)
A contribution to legal theories of accountability, this book offers pioneering research on the position of the individual in the EU's Economic and Monetary Union. Its premise is that the EU's response to the financial crisis placed undue emphasis on equality of Member States, to the detriment of political equality of citizens. As a remedy, this book reimagines legal accountability as the vehicle for achieving the common interest, by presenting a novel understanding of the relationship between solidarity and equality. Institutionally, the author argues that, by carrying out intensive review of the duty to state reasons, courts can ensure that decision-makers act in the common interest. The book explores judicial review in financial assistance, the monetary policy mechanisms of the European Central Bank, and the Single Supervisory Mechanism. Looking into the future, it tests its theoretical and normative propositions on the newly established Next Generation EU. This title is also available as Open Access on Cambridge Core.